Native goat and "Morada Nova" sheep performance in different pastures in Ceará - Fernandes, Antônio Amaury Oriá; Machado, Francisco Hélio Ferreira; Andrade, João Monteiro de Sales; Menezes, Fernando Antônio Bezerra de; Catunda, Amadeu Gladstone; Figueiredo, Elsio Antônio Pereira de (Pesquisa Agropecuaria Brasileira, 2014)
Native goat and Morada Nova sheep parturition, adult mortality and gemelarity rates were evaluated from 1977 to 1979, in three pasture types - native caatinga, cleared caatinga and buffelgrass (Cenchrus ciliaris L.). It was conducted at Iracema Farm of Empresa de Pesquisa Agropecuária do Ceará - EPACE - in Quixadá, CE, Brazil. Parturition rates were different for year, species, year x species and year x pasture type. Goats had 55.7%, 91.6%. and 70.8% of parturition, and sheeps 89.1%, 85.2% and 86.9% of parturition in 1977, 1978 and 1979, respectively. Adult mortality rates were affected by year, species, year x species and species x pasture type. Sheep survival was 87.6%, 98.0% and 85.1%, and for goats, 92.9%, 95.3% and 98.6% respectively for 1977, 1978 and 1979. Sheep mortality was greater in native caatinga pasture whereas goats were not affected by the pasture types. Gemelarity rates were different for species, goats with 43.0% and sheeps with 25.8%. Buffelgrass pasture carrying capacity was 350% higher than native caatinga and 182% than cleared caatinga pastures.